2022
DOI: 10.3390/jimaging8100278
|View full text |Cite
|
Sign up to set email alerts
|

Multimodality Imaging of the Neglected Valve: Role of Echocardiography, Cardiac Magnetic Resonance and Cardiac Computed Tomography in Pulmonary Stenosis and Regurgitation

Abstract: The pulmonary valve (PV) is the least imaged among the heart valves. However, pulmonary regurgitation (PR) and pulmonary stenosis (PS) can occur in a variety of patients ranging from fetuses, newborns (e.g., tetralogy of Fallot) to adults (e.g., endocarditis, carcinoid syndrome, complications of operated tetralogy of Fallot). Due to their complexity, PR and PS are studied using multimodality imaging to assess their mechanism, severity, and hemodynamic consequences. Multimodality imaging is crucial to plan the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 60 publications
0
8
0
Order By: Relevance
“…In this regard, cardiac MRI has demonstrated to be a reliable tool for the assessment of RV global longitudinal and radial strains in a population of patients with repaired Tetralogy of Fallot and may overcome some of the limitations of transthoracic echocardiography [ 24 ]. Moreover, it is reported that long-standing RV pressure overload may lead to myocardial fibrosis assessed on cardiac MRI, and this finding can possibly jeopardize the benefits of pressure overload relief [ 25 ]. However, in our cohort, we did not find significant differences in terms of RV functional recovery after BPV between younger and older children.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, cardiac MRI has demonstrated to be a reliable tool for the assessment of RV global longitudinal and radial strains in a population of patients with repaired Tetralogy of Fallot and may overcome some of the limitations of transthoracic echocardiography [ 24 ]. Moreover, it is reported that long-standing RV pressure overload may lead to myocardial fibrosis assessed on cardiac MRI, and this finding can possibly jeopardize the benefits of pressure overload relief [ 25 ]. However, in our cohort, we did not find significant differences in terms of RV functional recovery after BPV between younger and older children.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it gives detailed information about prosthetic valves, and it is also essential for surgical and transcatheter intervention planning. 20 To correctly visualize the pulmonary valve and its surrounding structures, the right heart chambers must be appropriately opacified using optimal imaging methodology and ECG-gated acquisitions: in particular, the split-bolus injection offers adequate attenuation for right heart chambers avoiding streak artifacts from high-attenuation contrast medium. 21 …”
Section: Diagnosismentioning
confidence: 99%
“…Both echocardiography and cardiac magnetic resonance (CMR) imaging are used to assess PR, with CMR flow quantification considered the benchmark standard. 23 , 24 Cross-sectional imaging is most reliable for the quantification of ventricular volumes and function in the tripartite RV. Cardiac magnetic resonance and CCT are both used to quantify ventricular volumes and function.…”
Section: Multimodality Definitions Of Pulmonary Valve Bioprosthetic V...mentioning
confidence: 99%